Association Between Fat Mass to Lean Body Mass Ratio and All-Cause Mortality Among Middle-Aged and Elderly Cancer Patients Without Obesity: A Multi-Center Observational Study in China - Xue, Hongmei; Du, Hongzhen; Xie, Ying; Zhai, Yijing; Song, Shiming; Luo, Bin; Qiu, Hong; Wang, Kunhua; Cui, Jiuwei; Song, Chunhua; Xu, Hongxia; Li, Wei; et al. (Frontiers in Nutrition, 2022)
Objective: We aimed to investigate the association of ratio between fat mass to lean body mass ratio (RFL), percentage of body fat (PBF), fat mass (FM) with mortality among middle-aged and elderly cancer patients without obesity. Methods: This prospective hospital-based cohort study comprised 3201 patients with stage I to IV cancer aged 40 years or above (mean age: 58 years old for female and 61 years old for male; mean length of follow-up was 1.67 years; the maximal follow-up length was 6.42 years). Fat mass, and percentage of body fat were measured by bio-electrical impedance analysis (BIA). Cox proportional hazard models were used and adjusted hazard ratios (HRs) were estimated. Results: We revealed a significant association between RFL and all-cause mortality among men aged ≥ 60 years after adjusting for confounders. Compared with those in the lowest tertile of RFL, elderly men in the medium and highest tertile had a 35% and 34% lower hazard of death from any cause, respectively. After additionally adjusted for CRP, HR of medium and high tertile of RFL became short of statistical significance (medium tertile: adjusted HRs (95% CI) =0.74 (0.46, 1.20); highest tertile: (adjusted HRs (95% CI) =0.84 (0.53, 1.33)). Among elderly women, RFL was significantly related to all-cause mortality only when the additional adjustment for CRP (medium tertile: adjusted HRs (95% CI) =2.08 (1.08, 4.01); highest tertile: adjusted HRs (95% CI) =0.90 (0.45, 1.81)). No significant association between RFL and all-cause mortality was observed among females or males aged less than 60 years. Conclusion: Our findings showed a significant non-linear association between RFL and all-cause mortality, which were observed only in elderly men, independent of body mass index and might be attenuated by their inflammation state.